Pengembangan Aplikasi Cashless Payment menggunakan Teknologi QR Code berbasis Android pada Kantin Dharma Wanita Filkom UB - Kelvin Anggatanata; Widhy Hayuhardhika Nugraha Putra; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Cashless payments are now starting to become a trend that is widely used in various places to make transactions. Cashless payments provide various advantages of cash payments, practical and convenient, time efficiency, no need to count change, easy recording of transactions, and many other advantages of non-cash cash payers. This study aims to develop methods of android-based non-cash payment systems using QR Code in the FILKOM UB canteen. QR Code is data information that has been made into two-dimensional images that can display data in the form of text developed by Denso Wave. QR Code can display information with its users. The Waterfall method is used in system development, which is implemented on the Android platform. The system was developed through several stages that discussed problems, literature study, needs analysis, and system design with the Unified Modeling Language, the implementation of the results of preparations made to Android using the Android SDK, React-native framework, real Firebase database. System testing is done using validation testing with the black box testing method and compatibility testing. The results of this test, obtained a validity level of 100% for 9 functional requirements and applications can be run on different versions of Android.